The performance of agricultural land management work in the context of needs, illustrated with an example of agricultural land consolidations - Dudzińska, Małgorzata (International Conference “Environmental Engineering”, 2017)
In the situation where Poland has been a member of the European Union since 2004, agricultural land consolidation has been co-financed with EU funds. This has resulted in an increase in the number of carried out land consolidations throughout Poland. Co-financing of this consolidation work has also introduced the need for a different understanding of the essence of agricultural land consolidation. According to Dacko (see Dacko 2006), the main goal of land consolidation should be to improve the quality of rural life, and not only to increase agricultural production. Land consolidation measures should be initiated to revive the countryside by encouraging continuous economic and political development of the local community, while protecting and rationally managing natural resources. The local community should participate democratically in land consolidation and in defining new forms of land use that make the most of the local potential. Currently in Poland, the choice of a location for the implementation of consolidation work not only depends on the farm land layout and land fragmentation also on the farmers who apply for the implementation of consolidation work in the particular area. Social acceptance is the key prerequisite for successful land consolidation. This fact has resulted in the agricultural land consolidation taking place not only in the areas in which the needs deter mined on the basis of the farm land layout and land fragmentation are most unfavorable. The paper comparatively analyses the determined needs as regards consolidation work in Poland, and the implementation of this work since 2004. The research employed the following methods: analysis and synthesis of the literature, field inventory, and research from the group of spatial-statistical approaches. The study area covered Poland, and in particular the selected region.